Implementation Of Learning Media Based On Artificial Intelligence Technology For Students Of Special School C - ., Haeruddin; Harimurti, Eka Rista; Harsono, Yhonanda; Fajarianto, Otto (Journal of Ecohumanism, 2025)
This article aims to provide an overview of the implementation of learning media based on artificial intelligence technology (AI) for Special School (SLB) C students and the impact of using learning media based on artificial intelligence technology on cognitive development in Special Schools (SLB) C. This research is qualitative research using literacy study methods. Data collection was carried out through examining data sources, namely articles from scientific journals and online news that were relevant to the research topic, which were then identified in depth and arranged in a theoretical framework to draw conclusions. The results of the research show that the implementation of learning media based on artificial intelligence (AI) technology in Special School (SLB) C students has a positive impact on cognitive development because it makes students more able to remember, convey opinions (communicative) and find it easier to learn. understand the material taught.